PROBLEMATIKA IMPLEMENTASI PENILAIAN AUTENTIK PADA MATA PELAJARAN AL-QUR’AN HADIS DI MTs NEGERI GANDUSARI BLITAR - Dita Dzata Mirrota; Desy Nailasari (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2020)
An authentic assessment is carried out comprehensively to assess the learning inputs, processes and outputs. Authentic assessment must reflect real-world problems, not the world of schools. This study aims to describe the problematics of the implementation of authentic assessment in the subject of the Qur'anic Hadith. This type of research is field research. The results of this study are the implementation of authentic assessment in the subjects of the Qur'an in Hadith in the MTsN Gandusari Blitar: the implementation of authentic assessment in the Blitar Gandsari State MTs requires improvement. Problems with authentic assessment implementation: more instruments and formats, a long time, the assessment process, assessment of attitudes that require accuracy, limited educators, inputs, and considerable costs. The solution given to the problem: conduct MGMP, workshops or guidance on authentic assessment, increase the number of educators, assess according to the provisions, certain parties who give their role, and get used to assess authentically properly and correctly.